Components of diabetes prevalence in Denmark 1996–2016 and future trends until 2030. Issue 1 (11th August 2020) - Carstensen, Bendix; Rønn, Pernille Falberg; Jørgensen, Marit Eika
Abstract : Introduction: Incidence rates of diabetes have been increasing and mortality rates have been decreasing. Our aim is the quantification of the effects of these on the prevalence and prediction of the future burden of diabetes. Research design and methods: From population-based registers of Denmark, we derived diabetes incidence and mortality rates and mortality rates for persons without diabetes for the period 1996–2016. Rates were modeled by smooth parametric terms using Poisson regression. Estimated rates were used to assess the relative contribution of incidence and mortality to changes in prevalence over the study period as well as for prediction of future rates and prevalence 2017–2040. Results: The major contributors to prevalence was increasing incidence (22%) and epidemiological imbalance between incidence and mortality (27%). The decrease in mortality rates over the period 1996–2016 contributes only 9% of the prevalent cases at 2016. We estimated that 467 000 persons in Denmark would be living with diabetes in 2030. The age distribution of patients in the period 2017–2030 is predicted to change toward older ages. The total number of persons needing diabetes care will increase by 67% over the next 13 years, an average annual increase of 4.0%. Conclusions: Lowering mortality among patients with diabetes even further is not likely to influence the prevalence substantially. Since the size and the increase in incidence of diabetes are major drivers of the increasing prevalence, the prevention of new cases of diabetes is required.